2016
DOI: 10.1002/mbo3.365
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the directionality of Escherichia coli formate hydrogenlyase: a membrane‐bound enzyme capable of fixing carbon dioxide to organic acid

Abstract: During mixed‐acid fermentation Escherichia coli produces formate, which is initially excreted out the cell. Accumulation of formate, and dropping extracellular pH, leads to biosynthesis of the formate hydrogenlyase (FHL) complex. FHL consists of membrane and soluble domains anchored within the inner membrane. The soluble domain comprises a [NiFe] hydrogenase and a formate dehydrogenase that link formate oxidation directly to proton reduction with the release of CO 2 and H2. Thus, the function of FHL is to oxid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
88
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(93 citation statements)
references
References 80 publications
4
88
0
1
Order By: Relevance
“…Depending on whether HCO3 or CO 2 was used for calculation, reaction enthalpies ranged from −8.1 to −16.3 kJ per mol, indicating that this part of the reaction energy was not exploited (Table ). Other authors demonstrated hydrogen production from formate with purified formate hydrogenlyase of E. coli (Pinske and Sargent, ). Here, 15.7 mM formate was added to the purified enzyme in the reaction chamber of a hydrogen‐sensing Clark electrode and maximal production of around 600 nmol hydrogen in 1.7 ml volume was observed, with a final formate concentration of 14.9 mM.…”
Section: Topic 4 Formate and Hydrogen Equilibriamentioning
confidence: 99%
See 3 more Smart Citations
“…Depending on whether HCO3 or CO 2 was used for calculation, reaction enthalpies ranged from −8.1 to −16.3 kJ per mol, indicating that this part of the reaction energy was not exploited (Table ). Other authors demonstrated hydrogen production from formate with purified formate hydrogenlyase of E. coli (Pinske and Sargent, ). Here, 15.7 mM formate was added to the purified enzyme in the reaction chamber of a hydrogen‐sensing Clark electrode and maximal production of around 600 nmol hydrogen in 1.7 ml volume was observed, with a final formate concentration of 14.9 mM.…”
Section: Topic 4 Formate and Hydrogen Equilibriamentioning
confidence: 99%
“…Here, 15.7 mM formate was added to the purified enzyme in the reaction chamber of a hydrogen‐sensing Clark electrode and maximal production of around 600 nmol hydrogen in 1.7 ml volume was observed, with a final formate concentration of 14.9 mM. The final concentrations of formate, hydrogen, and CO 2 (calculated from the consumed formate) were 14.9 mM, 353 µM and 840 µM respectively (Pinske and Sargent, ). From these values and the standard Gibbs’ free reaction energy of −3.4 kJ per mol (Eq. )…”
Section: Topic 4 Formate and Hydrogen Equilibriamentioning
confidence: 99%
See 2 more Smart Citations
“…Эта возможность просматривается в структуре HycD/HycC субъединиц Hyd-3 фермента, обладающих значительным сходством с респираторным комплексом НАДН:хиноноксидоредуктазы (Complex 1) [27,16,28], и продемонстрирована в экспериментах у двойных мутантов c делециями оперонов hya [Hyd-1] и hyb [13], проведенных при рН = 6.5 в ферментирующих условиях, что совпадает с условиями роста клеток в проточном хемостате [20] в отсутствие нитрита. В случае прямой транслокации протонов через FHL-1 комплекс, механизм формирования мембранного потенциала будет идентичен таковому с участием FHL-2 комплекса, который рассматривается далее.…”
Section: реконструкция молекулярно-генетического механизма формированunclassified